2009
DOI: 10.1111/j.1365-2249.2009.04057.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon signature gene expression is correlated with autoantibody profiles in patients with incomplete lupus syndromes

Abstract: SummaryInterferon (IFN) signature genes have been shown to be expressed highly in peripheral blood of patients with systemic lupus erythematosus (SLE), especially in the presence of active disease. However, the expression of this gene signature in individuals with incomplete forms of lupus and the pathogenic relationship between IFN signature genes and autoantibody production have not been explored fully. In the present study, we examined the gene expression and autoantibody profiles of patients diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 30 publications
10
85
1
2
Order By: Relevance
“…Indeed, in our investigation, the number of positive autoantibodies was the most significant (p<0.001) predictor of increased IFN-α activity in cases. A recent study demonstrated IFN-α activity associated with autoantibody positivity, a small study (n=24) showed exacerbated type I IFN signatures in incomplete lupus erythematosus patients whose autoantibody specificities had already class-switched to the pathogenic IgG isotype23 and a number of studies have noted the ability of autoantibody-containing immune complexes to drive type I IFN activation 24–27. While IFN-α activity is clearly important in the transition to classified SLE, it may not be a leading factor for the initial development of lupus-associated autoantibody specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in our investigation, the number of positive autoantibodies was the most significant (p<0.001) predictor of increased IFN-α activity in cases. A recent study demonstrated IFN-α activity associated with autoantibody positivity, a small study (n=24) showed exacerbated type I IFN signatures in incomplete lupus erythematosus patients whose autoantibody specificities had already class-switched to the pathogenic IgG isotype23 and a number of studies have noted the ability of autoantibody-containing immune complexes to drive type I IFN activation 24–27. While IFN-α activity is clearly important in the transition to classified SLE, it may not be a leading factor for the initial development of lupus-associated autoantibody specificities.…”
Section: Discussionmentioning
confidence: 99%
“…In general the presence of evolving autoantibody specificities, including antibodies to dsDNA, which have been observed to accrue prior to the onset of lupus, suggest the development of overt disease is likely 5,49,141 . A prominent interferon-induced gene signature and altered Th17/Treg ratios have been proposed as immunological markers of progression from incomplete lupus to systemic lupus erythematosus, but our understanding is limited 71,131 . Although not definitive, there is suggestive evidence that hydroxychloroquine can delay or prevent the development of fullblown lupus in patients presenting with an incomplete picture 62 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additional longitudinal evaluation of ILE patients, both in the interferon-high and interferon-low groups, are necessary to see if ILE patients with elevated interferon signatures are at higher risk of transition to SLE. (38) …”
Section: Introductionmentioning
confidence: 99%